THE RELATIONSHIP AMONGST STUDY OF READING HABITS, READING ATTITUDE, AND READING ACHIEVEMENT OF WATTPAD READER AT IAIN PALANGKA RAYA - Rizqa Aulia; Sabarun sabarun; Akhamad Ali Mirza (INOVISH JOURNAL, 2023)
This study investigated the relationship amongst study of reading habits, reading attitude, and reading achievement of Wattpad reader at IAIN Palangka Raya. This study used a quantitative method and a multiple linear regression design.This study involves 30 students of third and fifth semesters of English Department at IAIN Palangka Raya. The data are collected using questionnaire and test. The findings revealed that there is a positive relationship between students' reading habits (mean = 89.47) and attitudes (mean = 70,23) toward their reading achievement (mean = 87,33) as wattpad readers in the third and fifth semesters of the English Education Study Program at IAIN Palangka Raya. The effect of Students' Reading Habit (X1) on Students' Reading Achievement (Y) is 40%, while the effect of Students' Reading Attitude (X2) on Students' Reading Achievement (Y) is 42%. The combined effect of the independent variables on the dependent variable is then 82%. It meant that students' reading habits and reading attitudes have a relatively high influence on students' reading achievement. Therefore, reading habit and attitude can predict the successful language learning in reading achievement. Based on the findings, students should read more to improve their reading habits and attitudes. Teachers and lecturers, particularly in reading subjects, must pay closer attention to students' reading habits and attitudes. For future researchers to conduct research with a larger sample size and to focus not only on reading but also on other abilities such as writing, listening, and speaking.